Measurement of angular correlations of Compton-scattered gamma quanta from positron annihilation using GAGG:Ce scintillator matrices with single-side readout. (1st September 2022) - Parashari, S.; Bosnar, D.; Kožuljević, A.M.; Makek, M.
Abstract: We measured azimuthal correlations of the Compton-scattered gamma quanta from positron annihilation with two 8 × 8 matrices of Gadolinium Aluminum Gallium Garnet doped with Cerium. Each detector matrix contains 64 crystals of size 3 mm × 3 mm × 20 mm and it is read-out by a single Silicon Photo-multiplier (SiPM) array, with one SiPM matching one pixel. The studied single-side readout concept keeps the modules compact and cost-efficient on a large scale. Coincidence events were recorded using a Na-22 source placed between the modules. We clearly identify and reconstruct the Compton scattering events and we observe the excess of orthogonally scattered gammas over the ones with the parallel azimuthal angles. We present the measured azimuthal modulation factors for several kinematic selection criteria and different inter-pixel distances.